2021
DOI: 10.1097/phm.0000000000001692
|View full text |Cite
|
Sign up to set email alerts
|

The Physiatry Workforce in 2019 and Beyond, Part 1

Abstract: Objective The aim of the study was to describe the current physiatrist workforce in the United States. Design An online, cross-sectional survey of board-certified physiatrists in 2019 (N = 616 completed, 30.1% response) collected information about demographic and practice characteristics, including age, sex, practice area, practice setting, hours worked, patient characteristics, staffing, and work responsibilities. Physiatrists were stratified by substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…As the medical specialty of physiatry continues to grow in a changing healthcare environment of an aging population, expanding workforce of older adults, growing population of people with a disability, and increase in diversity, it is imperative that ongoing planning occurs for meeting the rehabilitation needs of individuals in the U.S. and in underserved areas (Dall et al, 2021; Forte et al, 2021). The numbers of individuals in need of rehabilitation modalities will continue to rise, creating ongoing need for the specialty of PM&R.…”
Section: Discussionmentioning
confidence: 99%
“…As the medical specialty of physiatry continues to grow in a changing healthcare environment of an aging population, expanding workforce of older adults, growing population of people with a disability, and increase in diversity, it is imperative that ongoing planning occurs for meeting the rehabilitation needs of individuals in the U.S. and in underserved areas (Dall et al, 2021; Forte et al, 2021). The numbers of individuals in need of rehabilitation modalities will continue to rise, creating ongoing need for the specialty of PM&R.…”
Section: Discussionmentioning
confidence: 99%
“…Current workforce projection models for PM&R lack information at the individual subspecialty level. Moreover, the data informing these models have inherent limitations 26‐29 . For example, self‐reported practice survey information used in recently published models, although valuable, is subject to drawbacks including response bias, a low response rate, and a potentially unrepresentative sample.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the data informing these models have inherent limitations. [26][27][28][29] For example, self-reported practice survey information used in recently published models, although valuable, is subject to drawbacks including response bias, a low response rate, and a potentially unrepresentative sample. Information on the numbers of available and filled subspecialty fellowship positions also provides an incomplete picture because it does not account for the high proportion of diplomates who obtain subspecialty certification through the practice track rather than the fellowship track.…”
Section: Disclosuresmentioning
confidence: 99%
“…A recent workforce modeling study concluded that the United States will continue to have a persistent shortfall of physiatrists unless there is a sufficient increase in physiatry residency and fellowship positions 38 . Furthermore, geographical imbalances continue to exist in part owing to the limited PM&R training opportunities in some areas of the United States (e.g., especially in rural areas) 38,39 . In addition to expanding the number of residency and fellowships positions, physiatric educational programs must be flexible and focused on the success of current and future physiatrists.…”
Section: Education/learning Environmentmentioning
confidence: 99%
“…38 Furthermore, geographical imbalances continue to exist in part owing to the limited PM&R training opportunities in some areas of the United States (e.g., especially in rural areas). 38,39 In addition to expanding the number of residency and fellowships positions, physiatric educational programs must be flexible and focused on the success of current and future physiatrists. Thoughtful and focused educational initiatives ranging from clinical knowledge to administration and leadership skills will help academic physiatrists navigate the challenges of the future, ensuring the relevance and impact of the field.…”
Section: Education/learning Environmentmentioning
confidence: 99%